Informal Learning Opportunities Matter: The Interprofessional Learning Experiences of Undergraduate Speech Pathology Students - Zhao, Disheng; Nagarajan, Srivalli; Nisbet, Gillian (International Journal of Practice-based Learning in Health and Social Care, 2015)
Despite increasing recognition of the importance of interprofessional learning (IPL) for interprofessional practice, it is unclear how and where speech pathology students are developing their interprofessional competencies within the university curriculum. This study aimed to clarify how interprofessional competencies develop in students by using a qualitative approach to explore speech pathology students’ perceptions of their university interprofessional learning experiences. Nine individual semi-structured interviews were conducted. Thematic analysis was used to analyse the data. Two major themes emerged: (i) occurrence of informal interprofessional learning (including informal IPL opportunities/context and its contribution to interprofessional learning experiences), and (ii) factors influencing interprofessional learning (role of placement, clinical educators and student’s motivation to engage in IPL activities). Participants reported valuing their interprofessional learning experiences, which were mainly informal interactions with professionals that occurred during clinical placements. The findings suggest that informal interprofessional learning experiences are a valuable source of interprofessional learning which can assist students to develop competencies for interprofessional practice. Recommendations for universities to more effectively support students’ interprofessional learning are provided.